2022
DOI: 10.46827/ejel.v7i5.4505
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating the “Dizi Gui” Into Efl Classrooms for Young Learners: A Study on Self-Regulation in Second Language Acquisition

Abstract: It is important to foster EFL young learners’ self-regulation in learning. This descriptive study investigates the effects of incorporating the Dizi Gui (Standards for being a good pupil and child) on EFL young learners’ self-regulation and discovers young learners’ attitudes towards the incorporation. A 51-item questionnaire was administered to 100 young learners at a center for foreign languages in a central city of Mekong Delta, and 6 of them participated in the semi-structured interviews. The quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…It is important to foster EFL young learners' self-regulation in learning. A descriptive study found that young learners self-regulate at an under-average level of frequency in their learning process, and incorporating the Dizi Gui (Standards for being a good pupil and child) can have positive effects on EFL young learners' self-regulation (Thu, 2022).…”
Section: Puzzles and Blocksmentioning
confidence: 99%
“…It is important to foster EFL young learners' self-regulation in learning. A descriptive study found that young learners self-regulate at an under-average level of frequency in their learning process, and incorporating the Dizi Gui (Standards for being a good pupil and child) can have positive effects on EFL young learners' self-regulation (Thu, 2022).…”
Section: Puzzles and Blocksmentioning
confidence: 99%